(untitled) (Global Journal of Management and Business Research, 2014)
The objective in this Paper is to expose the extend of the salary gate scandal in the Zimbabwean Parastatals sector, what the various stakeholders have said about the unraveling scandal and what remedial action has been taken against the perpetrators of the said scandal. Thereafter, the Author will proffer a Summary, Conclusion and Recommendation to wrap up the discourse.